Inquiry of the Practice of Leadership in Chengguan: A Study Based on the Ethnographic Research of Z City - Li, Hua; Li, Yifan (Frontiers in Psychology, 2022)
Based on an ethnographic case study in Z City, China over 18 years, we analyzed how different leadership impact different organization behavior in terms of work performance. We demonstrate Leadership acts as the internal driving force for an organization’s effective operation and develop five leadership perspectives with reference to prior study. Experience management (traditional management), scientific management, values leadership, trust cultural leadership and Ethic (Spiritual) leadership. Additionally, we propose three suggestions to improve the leadership with regard to Chengguan organization: the entrance for leaders’ appointment should be act serious, “position and treatment”-oriented leadership approaches need to be transformed into people-oriented leadership; and that leader should be encouraged to learn ethic(spiritual) leadership skills to be an ethic leader, in terms of authentic (honesty), trustworthiness, fairness, and conscientiousness. Rather “said one thing and did another”, mouthing empty slogans, and treat leadership as "you owe me, or I owe you" trading culture.